Designing and Creating a Synthetic Omega Oxidation Pathway in Saccharomyces cerevisiae Enables Production of Medium-Chain α, ω-Dicarboxylic Acids - Han, Li; Peng, Yanfeng; Zhang, Yuangyuan; Chen, Wujiu; Lin, Yuping; Wang, Qinhong (Frontiers in Microbiology, 2017)
Medium-chain (C8-C14) α, ω-dicarboxylic acids (α,ω-DCAs), which have numerous applications as raw materials for producing various commodities and polymers in chemical industry, are mainly produced from chemical or microbial conversion of petroleum-derived alkanes or plant-derived fatty acids at present. Recently, significant attention has been gained to microbial production of medium-chain α, ω-DCAs from simple renewable sugars. Here, we designed and created a synthetic omega oxidation pathway in Saccharomyces cerevisiae to produce C10 and C12 α,ω-DCAs from renewable sugars and fatty acids by introducing a heterogeneous cytochrome P450 CYP94C1 and cytochrome reductase ATR1. Furthermore, the deletion of fatty acyl-CoA synthetase genes FAA1 and FAA4 increased the production of medium-chain α, ω-DCAs from 4.690±0.088 mg/L to 12.177±0.420 mg/L and enabled the production of C14 and C16 α, ω-DCAs at low percentage. But blocking β-oxidation pathway by deleting fatty-acyl coenzyme A oxidase gene POX1 and overexpressing different thioesterase genes had no significant impact on the production and the composition of α,ω-dicarboxylic acids. Overall, our study indicated the potential of microbial production of medium-chain α, ω-DCAs from renewable feedstocks using engineered yeast.